Evaluation of intraocular and partial CO2 pressure in dogs anesthetized with propofol - Batista, Cristina Mendes; Laus, José Luis [UNESP]; Nunes, Newton [UNESP]; Patto Dos Santos, Paulo Sérgio [UNESP]; Oliveira Costa, Jorge Luiz (Wiley, 2000)
The effects of propofol on intraocular pressure (IOP) and end tidal CO2 (ETCO2) were studied because an elevation in the latter may alter IOP. Twenty dogs were divided into two groups (G1 and G2). G1 dogs were induced with 10 mg/kg (IV) of propofol followed by a 0.4 mg/kg/min continuous infusion of the same agent diluted in a 0.2% dextrose solution for 1 h. G(CAPS) 2 dogs served as the control group, where only dextrose solution was administered, under the same time intervals as in G1. Applanation tonometry (Tono-Pen) was used to determine IOP and ETCO2 as a method to determine partial CO2 pressure. Measurements were taken every 15 min for 1 h, with M1 occurring immediately before IV administration. IOP and ETCO2 were not statistically significant in either groups. Based on the results, it may be concluded that propofol does not alter IOP and ETCO2.
Keywords: Dogs; ETCO2; Intraocular pressure; Propofol